The effects of perception- vs. production-based pronunciation instruction. (February 2020) - Lee, Bradford; Plonsky, Luke; Saito, Kazuya
Abstract: While research has shown that provision of explicit pronunciation instruction (PI) is facilitative of various aspects of second language (L2) speech learning (Thomson & Derwing, 2015), a growing number of scholars have begun to examine which type of instruction can best impact on acquisition. In the current study, we explored the effects of perception- vs. production-based methods of PI among tertiary-level Japanese students of English. Participants ( N = 115) received two weeks of instruction on either segmental or suprasegmental features of English, using either a perception- or a production-based method, with progress assessed in a pre/post/delayed posttest study design. Although all four treatment groups demonstrated major gains in pronunciation accuracy, performance varied considerably across groups and over time. A close examination of our findings suggested that perception-based training may be the more effective training method across both segmental and suprasegmental features.